Languages at War
XV, 269 p.
Keywords: Emphasising the significance of foreign languages at the centre of war and conflict, this book argues that 'foreignness' and foreign languages are key to our understanding of what happens in war. Through case studies the book traces the role of languages in intelligence, military deployment, soldier/civilian meetings, occupation and peace building.